N/A: Ukraine between the EU and Russia - Doboš, Bohumil (Journal of Regional Security, 2023)
The political developments in Ukraine in the past two decades can be analyzed from numerous perspectives. This article highlights the systemic geopolitical outlook. By conceptualizing Ukraine as being located between two qualitatively different types of empires – the EU and Russia – it uncovers some of the systemic causes of the escalation of the Russian incursion into Ukrainian politics. It concludes that as long as the Westphalian empire overestimates its hard-power capabilities, the neomedieval alternative presents a more viable enlargement strategy.